DOES MARINE FISHING CAPTURE DECLINE IN NORTH COAST OF CENTRAL JAVA? - Supriharyono Supriharyono (JOURNAL OF COASTAL DEVELOPMENT, 2003)
Marine fisheries productivity has been studied in North coast of central Java. Study was carried out at four coastal regions, i.e Brebes, Pemalang, Jepara , and Rembang from July to October 2002. The primary and secondary data were collected covering the existing marine habitats, namely mangrove, sea grass meadows, coral reefs, and fishing and marine culture production. The result showed that most marine local habitats in the North coast of central Java, mainly in the studied sites were worse. Mangrove cover, from the total of 3,442.19 ha was only 979,8 (8,46%) in good condition, while remaining areas of 2,462,39 ha (71,54%) were in critical or bad condition. Similar trends were observed in the sea grass and coral reef habitats showing the decrease of living coral cover resulted in the decline in fishing capture production.